Chalcogenide thin films - Halenkovič, Tomáš (Univerzita Pardubice, 2019)
This thesis is focused on study of amorphous thin films of ternary Ge-Sb-Se and Ga-Sb-Se systems fabricated by co-sputtering technique for their potential applications in the field of nonlinear optics. General quality by means of morphology and topography, linear and non-linear optical properties and local structure of fabricated films depending on the composition are discussed. The limitation of these materials may lie in their photosensitivity under the near-bandgap light irradiation. Therefore, this aspect of co-sputtered thin films was also studied. In the frame of the thesis, optical properties and structure of quaternary Ge-Sb-Se-Te thin films fabricated by RF sputtering as a potential alternative to ternary systems were also studied.
Tenké chalkogenidové vrstvy
Keywords: amorfní chalkogenidy; naprašování; amorfní tenké vrstvy; optické vlastnosti; struktura; amorphous chalcogenides; sputtering; amorphous thin films; optical properties; structure